Determinants of the initiation and duration of breast-feeding. - Scott, Jane A. (Curtin University, 1997)
The primary objectives of this study were to determine the initiation and prevalence, up to six months post-partum, of breast-feeding amongst Perth women and to identify factors that influence the initiation and duration of breast-feeding. A self-administered baseline questionnaire was completed by 556 mothers prior to discharge. Those mothers who were breast-feeding at the time of completing the baseline questionnaire were followed-up by telephone interview at 2, 6, 10, 14, 18 and 24 weeks postpartum, or until they ceased to breast-feed.In total, 88.1% of mothers commenced breast-feeding whilst in hospital. On discharge from hospital 83.8% of women were breast-feeding either fully (77.7%) or partially (6.1%) but by six months this figure had decreased to 49.9% of mothers breast-feeding.Multivariate logistic regression analysis was used to determine which factors were associated with the initiation of breast-feeding. There was a strong association between the father's reported preference for breast-feeding and the initiation of breast-feeding (OR=10.18). The Cox's proportional hazards model was used to estimate the effect of independent variables on the duration of breast-feeding. The factor most strongly associated with breast-feeding duration was intended duration. Women who intended to breast-feed for less than four months were more likely to stop breast-feeding at any time compared with women who intended to breast-feed for at least four months (RR=5.01).The results of this study suggest that breast-feeding initiation and duration rates in Perth have remained relatively stable over the last decade. However, breast-feeding duration continues to fall well short of the target of 80% of infants being either partially or fully breast-fed at six months. Recommendations are made for interventions which actively promote increased breast-feeding duration. In particular, emphasis should be placed on those strategies which will influence intended duration; influence the attitudes and beliefs of the mother's support network, particularly partners; and promote breast-feeding as the social norm.